A mind and its time the development of Isaiah Berlin's political thought - Cherniss, Joshua L. 1979- (Oxford University Press, 2013)
A detailed study of Isaiah Berlin: historian, philosopher, and political theorist. Situates his evolving ideas in the context of British society and world politics. Offers a new interpretation of Berlin's influential writings on liberty and his debts to philosophy, and makes clear his relationship to the political debates of his times
Includes bibliographical references and index
Keywords: Berlin, Isaiah / 1909-1997; Berlin, Isaiah / 1909-1997 / Philosophy; Berlin, Isaiah -- 1909-1997; Politische Philosophie; Political science / Philosophy; Philosophie; Politische Wissenschaft